Methods and Prospects for Determination of Mycotoxins in Medicinal Herbal Raw Materials (Review) - O. V. Trineeva (Разработка и регистрация лекарственных средств)
Introduction. Mycotoxins (MT) are secondary metabolites of microscopic mold fungi with pronounced toxic properties.Text. Currently, the development of express methods for determining the content of MT with mutagenic, teratogenic and carcinogenic properties is of particular importance in the food and pharmaceutical industries. The creation of methods for their analytical control continues to be the focus of attention of the largest international organizations (IUPAC, AOAC International and IFJU), specialized national organizations of the EU and the USA, as well as academies and ministries of many countries of the world. By the Decree of the President of the Russian Federation (RF), the Doctrine of Food Security of the RF № 120 dated January 30, 2010 was approved. The Ministry of Agriculture of the RF issued an order «On the implementation of the state veterinary laboratory monitoring plan» № 780 dated May 30, 2003. In our country, MT studies, according to the plan Monitoring and Recommendations of the EU Commission are limited to determining the content of six tested MTs - the sum of aflatoxins (AFL), ochratoxins (OT), zearalenone (ZEA), trichothecenes (TT), patulin (P), T-2 toxin in agricultural raw materials, food products and feed. MTs are natural pollutants not only of grains of cereals, legumes, sunflower seeds, as well as vegetables and fruits, but also of medicinal plant materials (MPM), as well as pharmaceutical substances of plant origin, in particular, such as fatty vegetable oils widely used in pharmacy in as independent drugs, as well as auxiliary components for the production of drugs, dietary supplements, solvents for injection drugs, etc. In the RF, the MT content in MPM is not yet standardized. It is almost impossible to prevent contamination of the MPM MT, therefore, strict control of these substances is necessary. However, this problem and the need to introduce such a study into the list of indicators for evaluating the quality of MPM requires an in-depth study and an assessment of the degree of its infection. In addition, standard methods for determining normalized MTs are usually not designed to detect transformed forms, and their content remains unaccounted for. Therefore, MT metabolites modified by a medicinal plant are called masked (conjugated, transformed) MT plants, the content of which also needs to be evaluated. MTs can also form during storage of MPM under the action of microscopic fungi developing in them. Since the basis for obtaining herbal medicines are medicinal plants, which are raw materials that are most contaminated with various microorganisms, viruses, and molds, not only MPM, but also almost all substances and herbal medicines (HM) can be infected. It has been shown that MTs remain in dried MPM for more than 100 years. It was found that a lot of MPM densely seeded with Deuteromycetes class molds, which can be detected by microscopic analysis. The aim of this work was to systematize the methods for determining the main MT based on the analysis of domestic literature for their possible further use in assessing the quality of MPM and HM based on it.Conclusion. MTs adversely affect the body of animals and humans and are difficult to decontaminate. MTs may be present in MPM without visible mold growth. MT does not lose toxicity for many years. It is not possible to completely eliminate the formation of MT in raw materials, therefore, the task of controlling its quality of services is to identify the presence of MT and compare the detected amount with the norms of maximum content. The content of MT in MPM is currently not determined in the RF by the RF GF XIV ed. However, by the decision of the Council of the Eurasian Economic Commission dated January 26, 2018 №15, the Rules of Good Practice for the cultivation, collection, processing and storage of raw materials of plant origin were approved, which stipulate the inadmissibility of mold formation during the primary processing, storage and transportation of cattle. Therefore, the accumulation of experimental material, as well as the development of pharmacopoeial methods for the analysis of MPM, constantly tightening quality requirements, can lead to the inclusion of this indicator in pharmacopoeial articles (PA). In this connection, it was interesting to conduct a review of existing methods of MT analysis, with their possible subsequent inclusion in the GPA and PA. The traditional methods of MT analysis are physicochemical methods. The most widely used chromatographic methods: HPLC, GLC using various detectors (mass spectrometric, fluorescence, amperometric, etc.). TLC occupies a special place among the separation methods. These methods, of course, are able to provide sufficient specificity and the necessary sensitivity of the determination, however, they are expensive, designed primarily for specialized and well-equipped stationary laboratories, and also require highly qualified personnel. None of them can also be attributed to express methods. The complexity of determining MT in MPM is associated with long and laborious sample preparation, as well as with the use of expensive highly sensitive methods (HPLC, GLC), which cannot be applied directly at the place of production and processing of MPM. The most promising are immunochemical test methods for determining MT, based on the immunochemical reaction between the antibody and antigen. It was shown that the high specificity and the possibility of detecting MT in low concentrations in combination with the existing diverse instrumentation make it possible to consider immunochemical methods of analysis as the most promising for wide practical use.